Multi-platform advertising strategies in the global marketplace - Yang, Kenneth C. C. (IGI Global, 2018)
"This book is on the latest multi-platform advertising strategies in the global marketplace. It is accessible to advertising, marketing communications, and marketing practitioners to better understand this emerging phenomenon. This book is also useful for researchers who are interested in studying the global impacts of multi-platform media on the advertising/marketing communications industry"-- Provided by publisher.